Fine‐root production and litterfall: main contributions to net primary production in an old‐growth evergreen broad‐leaved forest in southwestern Japan. Issue 5 (23rd July 2015) - Van Do, Tran; Sato, Tamotsu; Saito, Satoshi; Kozan, Osamu
Abstract: Net primary production (NPP) is an important index for evaluating the patterns, processes, and dynamics of carbon cycling in forest ecosystems. In this study, we estimated the NPP in a warm‐temperate old‐growth evergreen broad‐leaved forest in southwestern Japan. The estimation was based on four compartments: aboveground stand increment (ΔM), aboveground litterfall (Lf), fine‐root production (Fr), and coarse root increment (ΔCr). The data for ΔM and ΔCr were collected from a permanent 200 × 200 m 2 plot over a 4‐year interval, while Lf and Fr were collected over a 1‐year interval. The NPP was 4.65 g m −2 day −1, of which ΔM accounted for 25.2 %, Lf accounted for 38.7 %, Fr accounted for 33.4 %, and the remaining 2.7 % was attributed to ΔCr. There was a significant regression between aboveground litterfall and fine‐root production (R 2 = 0.65, P < 0.05). Fine‐root decomposition (0.66 g m −2 day −1 ) accounted for 14.2 % of the NPP, leading to a higher belowground NPP in the present study compared with that in other forests. We conclude that an estimation of the decomposition of dead fine‐roots by the continuous inflow method must be included to improve the accuracy of NPP estimations for forest ecosystems.